La automedicación como un factor de riesgo de salud pública : análisis en una comunidad vulnerable en Medellín-Colombia (2014)
ABSTRACT: Studies and interventions around the self-medication are still insufficient, although in recent years it has been paying attention to this attitude and practice because of the negative impact on public health and economy. This problem could be more serious in a poor community. Objective: To educate on risk factors associated with self-medication in the community of Vallejuelos neighborhood through academic practices aimed at health promotion and disease prevention with the focus on the early formative research. Methods: This is a type Participatory-Action-Research (PAR) study, which techniques used were the participant observation, the field notes, a structured survey directed and a oriented educational intervention community from the perspective of a service and to provide comprehensive pharmaceutical care; in order to contribute from the axes mission of the university (research, teaching and extension) to improve the living conditions of the population in critical conditions. Results: It can be inferred that implications, risks and consequences of self-medication are unknown for the community of Vallejuelos, coupled with poverty and lack of education in holistic health. Conclusions: The attitude and practice of self-medication are associated with the vulnerability of populations, but it is a risk factor that induces public health problems; the Colombian state has not assumed control drug policy responsibility towards negative historical consequences of this thoughtless behavior. From this perspective, the pharmacist has an important social function in the prevention of this socio-cultural behavior.